OptimizationofTemperatureandDryingTimeofDragonFruitPeel Powder Using Response Surface Methodology - Andika Putra Setiawan; Danu Indra Wardhana; Oppy Valencia Indrian (Universitas Darussalam Gontor, 2024)
Dragon fruit is one of the fruits that has high economic value with good cultivation prospects in Indonesia, making it one of the most recommended by many people because it contains lots of vitamins. Dragon fruit skin has many benefits but has not been utilized optimally.Post-harvesthandlingeffortsneedtobedonetoextendthe shelf life of dragon fruit skin,onewaythatcanbedoneisthroughthedryingprocesstoreducewater content so that it can inhibit microbial growth and have a longer shelf life. The purpose of this study is to determine the effect of combination temperature and drying time, water content, color and organoleptic of dragon fruit skin powder. Optimization of temperature and drying time was analyzed using Response Surfase Methodology (RSM) at temperatures of 60°C, 70°C and 80°Cwith 5-, 6-, and 7-hours duration. Results showed that the optimal temperature for drying processofdragonfruitskinwasatatemperatureof79.47°Cwith5hoursduration.Theoptimal yield produced at the best temperature and drying time was 16,09% with a water content of 4.63%. In the color test of sample with combination temperature 600C and 6 hours duration showed the highest brightness of 65.6 and the results of the organoleptic test showed that temperature and drying time had a significant effect on the color and aroma of dragon fruit skin powder